ASME-JSME-KSME 2011 Joint Fluids Engineering Conference: Volume 1, Symposia – Parts A, B, C, and D 2011
DOI: 10.1115/ajk2011-06077
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Design of the Volute of a Centrifugal Pump Using CFD

Abstract: The objective of this paper is to develop the shape of an existing volute so that the radial forces in off-design condition become minimum. For this purpose 3-D inverse design method based on the 3-D viscous flow calculations was applied to re-design the geometry of the volute of a low specific speed pump. Various aspects of the geometry change independently to achieve the best one which produces less radial force in off design conditions. Measurements included time-averaged values of velocity and static press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…7 showed that radial force depends on the geometry of the region where the gap between impeller and volute is small, including both tongue shapes and blade-tongue gap. More recently, Torabi and Nourbakhsh 8 studied the effects of volute geometrical factor variation on radial force. They observed that the gap between impeller and tongue severely affects the radial force.…”
Section: Introductionmentioning
confidence: 99%
“…7 showed that radial force depends on the geometry of the region where the gap between impeller and volute is small, including both tongue shapes and blade-tongue gap. More recently, Torabi and Nourbakhsh 8 studied the effects of volute geometrical factor variation on radial force. They observed that the gap between impeller and tongue severely affects the radial force.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of manufacturing and cost analysis, the tangential diffuser is more suitable, and based on the latest study, the hydraulic forces created in the tangential diffuser are less than those of the radial one. 24
Figure 5.Parameters of volute with a tangential diffuser.
…”
Section: Different Shapes Of Volute Cross-sectionmentioning
confidence: 99%
“…Their research showed that volute with round cross section gives more head and efficiency in comparison with trapezoidal and rectangular cross sections. More recently, Torabi and Nourbakhsh [9] studied the effects of some volutes geometrical factor variation on radial force. They found that the gap between impeller and tongue severely affects the radial force.…”
Section: Introductionmentioning
confidence: 99%